On the temporary and the permanent business of friendly societies, with some suggestions for making the latter secure through the agency of the Post Office Insurance and Savings Bank departments - Hancock, William John (Statistical and Social Inquiry Society of Ireland, 1875)
Friendly societies are formed to enable labourers by co-operation to guard against the vicissitudes of life?such as temporary want of employment, temporary sickness, old age, and death. Provision for temporary want of employment and temporary sickness may be considered as somewhat analogous to fire insurance, that is to say, in individual cases the contract ends and the claim on the funds of the society ceases with the close of the year or shorter term for which contribution is paid. Each payment of contribution may be considered as a new contract for another term; and so far as sickness is concerned, the rates of contribution are either the same for all ages within the ordinary working period of life, or increase but little, as it is found that the average amount of sickness suffered at each age is nearly uniform from age 16 to about 40; then there is some increase up to about 60; after winch the increase of average sickness becomes considerable. It does not therefore appear to be necessary for societies offering these benefits only to have large reserve funds. Probably a year's income in hand would be sufficient. Such a society having too large funds would run a risk of being broken up by unscrupulous members, for the sake of dividing funds accumulated by the prudence of former members.
Read before the Society, 22 June 1875
Keywords: Friendly societies; Post Office Insurance and Savings Bank; 314.15